MTHFD1 Regulates Autophagy to Promote Growth and Metastasis in Colorectal Cancer via the PI3K‐AKT–mTOR Signaling Pathway - Zhihao Li; Haoxian Ke; Jiawei Cai; Shubiao Ye; Junfeng Huang; Chi Zhang; Ming Yuan; Ping Lan; Xianrui Wu (Cancer Medicine)
ABSTRACT Objectives Methylenetetrahydrofolate dehydrogenase 1 (MTHFD1) is the enzyme with the activities of methylenetetrahydrofolate dehydrogenase, methylenetetrahydrofolate cyclohydrolase, and formyltetrahydrofolate synthetase. Our aim was to elucidate the function of MTHFD1 in colorectal cancer (CRC). Methods In vitro assessments of the proliferation, invasion, and migration abilities of CRC cells were conducted using Immunohistochemistry, Transwell invasion assays, Western blot (WB), and Cell counting Kit‐8 assays. WB was also utilized to measure autophagy protein levels and PI3K‐AKT‐mTOR signaling pathway expression. Furthermore, the role of MTHFD1 was evaluated in vivo by using subcutaneous xenograft tumor models and lateral tail vein metastasis models of human CRC in nude mice. Results Overexpression of MTHFD1 promoted the abilities of tumorigenesis and metastasis in CRC in vitro and in vivo and reduced autophagy, attributing to the PI3K‐AKT‐mTOR signaling pathway in CRC cells. In contrast, the down‐regulation of MTHFD1 increased autophagy and suppressed their proliferation, migration, and invasion. Conclusions MTHFD1 can modulate the PI3K‐AKT‐mTOR signaling pathway to suppress autophagy and stimulate tumorigenesis and metastasis.